2012
DOI: 10.1029/2011sw000750
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 100‐year geomagnetically induced current scenarios

Abstract: .[1] A series of 100-year extreme geoelectric field and geomagnetically induced current (GIC) scenarios are explored by taking into account the key geophysical factors associated with the geomagnetic induction process. More specifically, we derive explicit geoelectric field temporal profiles as a function of ground conductivity structures and geomagnetic latitudes. We also demonstrate how the extreme geoelectric field scenarios can be mapped into GIC. Generated statistics indicate 20 V/km and 5 V/km 100-year m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
268
4
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(298 citation statements)
references
References 53 publications
24
268
4
2
Order By: Relevance
“…It can be characterized only by the morphology of the already recorded storms in the vicinity of each infrastructure (e.g., at Ebro Observatory for the northeastern Spanish power grid) and assumes that new periods of high activity will be reasonably comparable. Recent studies [Thomson et al, 2011;Pulkkinen et al, 2012] use extreme value statistics to explore the variations that might be observed every 100 or 200 years, but it must be taken into account that only one decade of digital magnetic data falls far short of the required duration to provide robust assessments even of the 1-in-100-years risk.…”
Section: Discussionmentioning
confidence: 99%
“…It can be characterized only by the morphology of the already recorded storms in the vicinity of each infrastructure (e.g., at Ebro Observatory for the northeastern Spanish power grid) and assumes that new periods of high activity will be reasonably comparable. Recent studies [Thomson et al, 2011;Pulkkinen et al, 2012] use extreme value statistics to explore the variations that might be observed every 100 or 200 years, but it must be taken into account that only one decade of digital magnetic data falls far short of the required duration to provide robust assessments even of the 1-in-100-years risk.…”
Section: Discussionmentioning
confidence: 99%
“…Such statistics would be useful in achieving deeper understanding of local ground conductivities in specific areas, and the overhead ionosphere current systems that can develop in geomagnetic disturbances. Studies of this nature include Lanzerotti et al (1993) and Pulkkinen et al (2012). The lengthy data set of Rooney (1949) has never been analyzed in a statistical manner.…”
Section: Technologies Based Upon Long Conductorsmentioning
confidence: 99%
“…This ejection was not Earth directed, but it provided researchers with an opportunity to study a space weather event that could have had deleterious consequences [ Baker et al ., 2013 ;Ngwira et al , 2013 ]. Together with historical data from ground observatories, this type of analysis informs scenario modeling of extreme events [e.g., Pulkkinen et al , 2012 ], and it is guiding the development of geomagnetic disturbance standards, such as those mandated by FERC.…”
Section: Extreme Eventsmentioning
confidence: 99%
“…This relationship can be used to forecast the future likelihood of magnetic storms across a range of intensities. Because extremely intense magnetic storms [e.g., see Pulkkinen et al , 2012 ] are, by defi nition, rare, retrospective statistical inferences end up being made from historical records of a small number of intense storms [e.g., Love , 2012 ].…”
Section: Extreme Eventsmentioning
confidence: 99%